Generalized verrucosis in a patient with GATA2 deficiency. (May 2014) - West, E.S.; Kingsbery, M.Y.; Mintz, E.M.; Hsu, A.P.; Holland, S.M.; Rady, P.L.; Tyring, S.K.; Grossman, M.E.
Summary Generalized verrucosis is a characteristic of several genetic and immunodeficiency disorders including epidermodysplasia verruciformis; warts, hypogammaglobulinaemia, infections and myelokathexis (WHIM) syndrome; warts, immunodeficiency, lymphoedema and anogenital dysplasia (WILD) syndrome; severe combined immune deficiency and HIV, among others. In recent years, it has been consistently recognized in patients with GATA2 deficiency, a novel immunodeficiency syndrome characterized by monocytopenia, B‐cell and natural killer‐cell lymphopenia, and a tendency to develop myeloid leukaemias and disseminated mycobacterial, human papillomavirus (HPV) and opportunistic fungal infections. Mutations in GATA2 cause haploinsufficiency and track in families as an autosomal dominant immunodeficiency. GATA2 is a transcription factor involved in early haematopoietic differentiation and lymphatic and vascular development. We describe a case of generalized verrucosis with HPV type 57 presenting in a young man with GATA2 deficiency. GATA2 deficiency is a novel dominant immunodeficiency that is often recognized later in life and should be considered in the differential diagnosis of patients with generalized verrucosis.